SEJARAH PERKEMBANGAN BANDARA JAPURA KECAMATAN LIRIK KABUPATEN INDRAGIRI HULU PROVINSI RIAU 1954-2018 - Nurliza Sembiring; Isjoni Isjoni; Tugiman Tugiman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: In the past the airport was used as air transportation for the benefit of large companies in Riau. And at this time the airport is not only for the benefit of large companies, but for traveling and making it easier for people to reach destinations with a short time. Historically, the development of Japura Airport has experienced developments and changes from time to time. Japura Airport was previously managed by the oil company PT. Standard Vacuum Petroleum, Mij (PT.Stanvac). On September 1, 1954 Japura Airport was officially handed over by the Standard Vacuum Petroleum Mij by Gerard L. McCoy, General Representative of the Stanvac Company in Indonesia to J.M. Minister of Transportation Prof. Ir. Roosseno. The research objectives are 1) To find out the history of the birth of Japura Airport, 2) To find out the classification of Japura Airport, 3) To determine the progress of Japura Airport flights, 4) To find out the efforts of Japura Airport in overcoming commercial flights like now. The method used is a qualitative method with a historical approach and data collection techniques in the form of interviews, observation and documentation. Key Words: History, Development, Japura Airport, Indragiri Hulu.